THE USE OF FTA’S STRATEGIES BY LECTURERS IN LISTENING SUBJECT - Masykur Rauf (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aimed at finding out the kinds of FTA strategies (positive and negative politeness) used by lecturers in lecturing listening comprehension and the effects of polite expressions used by lecturers on students. The researcher used descriptive qualitative research and applied a purposive sampling technique in collecting valid data. The subject of this research was one lecturer in the English and Literature Department of the Adab and Humanities Faculty. The researcher applied classroom observation by recording the lecturer’s activities and analyzed them through Brown and Levinson’s theory of politeness strategies (FTA). The researcher found some polite expressions of strategies that the lecturer used which are divided into two types. First, Positive Politeness (PP) such as noticing and attend the hearer, greetings, exaggerating, intensifying the interest of the hearer, using in-group identity makers, seeking agreement, presupposing/raising/asserting common ground, including both speaker and hearer in the activity, giving or asking reasons, assume or assert reciprocity and giving gifts to the hearer (goods, sympathy); and Negative Politeness (NP) such as Being conventionally indirect, Questions, Minimize the imposition, Giving deference, Nominalize. The effects on students are: being motivated in their study, student attitude (affective), respect for the lecturer, self-confidence, being active and attending the learning process, and honesty.